Rapid Pituitary Apoplexy Regression: What Is the Time Course of Clot Resolution? - Devon L. Jackson; Jamie J. Van Gompel (Case Reports in Radiology)
A 29-year-old male patient with a functioning pituitary macroadenoma is discussed. The pituitary mass was detected by MRI after the patient presented with sudden onset of headache, suggestive of an apoplectic event. The headache resolved with analgesic medications. Within a follow-up period of one week, the pituitary mass had spontaneously regressed to nearly half its original size without any therapy. The patient never reported any visual complaints and displayed no signs of hypopituitarism. Elevated prolactin levels were present. Seven weeks after the initial event, the pituitary mass showed continued regression on MRI. Prolactin levels remained elevated. This case provides a unique look at the rapid spontaneous regression of mass effect that may occur following apoplexy of a pituitary adenoma.